Three-dimensional composites with nearly isotropic negative Poisson's ratio by random inclusions: Experiments and finite element simulation. (8th February 2022) - Zhang, Minglonghai; Hu, Hong; Kamrul, Hasan; Zhao, Shuaiquan; Chang, Yuping; Ho, Mabel; Karim, Nazmul
Abstract: Composites with negative Poisson's Ratio (NPR), also known as auxetic composites, are of great interests due to excellent properties. Auxetic composites of various types have been developed, however most of them have anisotropic NPR behaviour. This paper reports a new type of three-dimensional (3D) composites with nearly isotropic NPR by randomly embedding rigid re-entrant equilateral triangle inclusions into soft matrix. Four types of inclusions with different structural parameters including re-entrant angle, prism length and rib thickness were first made from two types of carbon fibre prepregs, and then embedded into silicone rubber matrix with different inclusion numbers to fabricate 3D composites with various volume fractions of inclusions. Both experimental and finite element analyses were conducted to investigate the deformation behaviours under compression and the effects of different structural parameters and materials. The results show that the NPR of the composites can be realised with suitable structural parameters and properties. The lowest NPR of −0.19 was obtained via embedding 6 mm length inclusions made of one-layer 3K twill weave carbon fibre prepreg with an inclusion number of 800. The study provides a new approach for the development of 3D composites with isotropic NPR for the practical applications of auxetic materials. Graphical abstract: Image 1